Unveiling the Role of Cathepsins on Lung Function in Chronic Obstructive Pulmonary Disease: A Mendelian Randomization Analysis - Zhang X; Li X; Song S; Miao C; Yan L; Xu X; Liu Q (International Journal of COPD, 2025)
Xuemin Zhang,1– 4 Xintong Li,1– 4 Shuang Song,1– 4 Changhong Miao,4 Long Yan,4 Xiaolong Xu,1– 3 Qingquan Liu1– 3 1Beijing Hospital of Traditional Chinese Medicine, Capital Medical University, Beijing, 100010, People’s Republic of China; 2Beijing Institute of Traditional Chinese Medicine, Beijing, 100010, People’s Republic of China; 3Beijing Key Laboratory of Basic Research with Traditional Chinese Medicine on Infectious Diseases, Beijing, 100010, People’s Republic of China; 4Tianjin University of Traditional Chinese Medicine, Tianjin, 301617, People’s Republic of ChinaCorrespondence: Xiaolong Xu, Email xiaolong_xu3013@126.com Qingquan Liu, Email liuqingquan_2003@126.comBackground: Cathepsins are a group of proteases that can degrade the extracellular matrix of the lungs, leading to lung tissue destruction and remodeling in chronic obstructive pulmonary disease (COPD). However, the causal relationship between cathepsins and COPD remains unclear.Methods: We performed a two-sample Mendelian randomization (MR) analysis using genetic instruments for nine cathepsins (B, E, F, G, H, L2, O, S, and Z) and lung function measures (FVC, FEV1, FEV1/FVC, and PEF) in COPD. The MR analysis was conducted and reported as conducted and reported in accordance with the STROBE-MR Statement. We employed various MR methods and conducted sensitivity analyses to validate the results.Results: We found a significant association of cathepsin B with PEF (IVW beta = 0.016, 95% CI = 0.007 to 0.024, P = 2.83E-4), the FEV1/FVC ratio (IVW beta = 0.014, 95% CI = 0.004 to 0.023, P = 0.004), and FEV1 (IVW beta = 0.010, 95% CI = 0.002 to 0.018, P = 0.012) in COPD. These associations were consistent across different MR methods and robust to pleiotropy and heterogeneity. Multivariate MR analysis confirmed the independent effect of cathepsin B on lung function after adjusting for other cathepsins. Reverse MR analysis and colocalization analysis showed no evidence of reverse causality or shared genetic pathways with smoking.Conclusion: Our study suggested that elevated cathepsin B levels may reduce the risk of lung function decline in COPD. Targeting cathepsin B and its inhibitors could be a potential therapeutic strategy for COPD. Reduced serum levels of cathepsin B may serve as a biomarker of progressive decline in lung function in patients with COPD. However, further studies are needed to elucidate the underlying mechanisms and clinical implications of these findings.Keywords: cathepsins, chronic obstructive pulmonary disease, lung function, Mendelian randomization, causal relationship